2020
DOI: 10.1038/s41389-020-00256-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumour suppressor 15-hydroxyprostaglandin dehydrogenase induces differentiation in colon cancer via GLI1 inhibition

Abstract: Inflammation is an established risk factor for colorectal cancer. We and others have shown that colorectal cancer patients with elevated cysteinyl leukotriene receptor 2 (CysLT 2 R) and 15-hydroxyprostaglandin dehydrogenase (15-PGDH) levels exhibit good prognoses. However, both CysLT 2 R and 15-PGDH, which act as tumour suppressors, are often suppressed in colorectal cancer. We previously reported that leukotriene C 4 (LTC 4)-induced differentiation in colon cancer via CysLT 2 R signalling. Here, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…The gap junction α (GJA) family has been demonstrated to be involved in the cellular proliferation and metastasis of gastric cancer and breast cancer [ 31 , 32 ]. In the current study, we found that CYSLTR2 [ 33 , 34 ], CYP4Z1 [ 35 ], LINC00324 [ 36 ], and PTCSC3 [ 37 ] have shown a close relationship with the initiation and development of tumors and also with the prognosis of the COAD patients.…”
Section: Discussionmentioning
confidence: 96%
“…The gap junction α (GJA) family has been demonstrated to be involved in the cellular proliferation and metastasis of gastric cancer and breast cancer [ 31 , 32 ]. In the current study, we found that CYSLTR2 [ 33 , 34 ], CYP4Z1 [ 35 ], LINC00324 [ 36 ], and PTCSC3 [ 37 ] have shown a close relationship with the initiation and development of tumors and also with the prognosis of the COAD patients.…”
Section: Discussionmentioning
confidence: 96%
“…In our earlier studies, we provided first evidence that LTC 4 , via CysLT 2 R signaling, can induce 15-PGDH expression through the activation of the JNK/AP-1 pathway, and this activation in turn prompts the differentiation of CC cells [ 24 ]. In a follow-up study, we revealed that the induction of 15-PGDH by LTC 4 /CysLT 2 R signaling axis in CC cells downregulated GLI1 and induced differentiation in CC cells [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracted protein was used for western blot analysis of the following proteins: E-Cadherin (#3195, Cell Signaling Technology, Danvers, MA, USA); vimentin (#5741, Cell Signaling Technology, Danvers, MA, USA); CysLT 1 R (NBP2-92396; Novus Biologicals, Centennial, CO, USA). α-Tubulin (sc-8035; Santa Cruz Biotechnology, Heidelberg, Germany) antibodies were used for western blot experiment [ 54 , 62 ].…”
Section: Methodsmentioning
confidence: 99%